Associations between pre- and postnatal exposure to air pollution and lung health in children and assessment of CC16 as a potential mediator - Stapleton, Anna; Casas, Maribel; García, Judith; García, Raquel; Sunyer, Jordi; Guerra, Stefano; Abellan, Alicia; Lavi, Iris; Dobaño, Carlota; Vidal, Marta; Gascon, Mireia (Environmental research, 2022)
Early life exposure to air pollution can affect lung health. Previous studies have not assessed the implications of both pre- and postnatal exposure to air pollutants on lung function at repeated ages during childhood. In addition, there is the need to identify potential mediators of such effect. To longitudinally assess the association between pre- and postnatal air pollution exposure and lung function during childhood. We also aimed to explore the role of Club cell secretory protein (CC16) as a potential mediator in this association. We included 487 mother-child pairs from the INMA (INfancia y Medio Ambiente) Sabadell birth cohort, recruited between 2004 and 2006. Air pollution exposure was estimated for pregnancy, pre-school age, and school-age using temporally adjusted land use regression (LUR) modelling. Lung function was measured at ages 4, 7, 9 and 11 by spirometry. At age 4, serum CC16 levels were determined in 287 children. Multivariable linear regression models and linear mixed modelling were applied, while considering potential confounders. Prenatal exposure to Particulate Matter (PM)10 and PMcoarse had the most consistent associations with reduced lung function in cross-sectional models. Associations with postnatal exposure were less consistent. Increasing CC16 levels at 4 years were associated with an increase in FEF25-75 (β = 120.4 mL, 95% CI: 6.30, 234.5) from 4 to 11 years of age. No statistically significant associations were found between pre- or postnatal air pollution and CC16 at age 4. Increasing levels of air pollution exposure, particularly prenatal PM10 and PMcoarse exposure, were associated with a reduction in lung function. We were not able to confirm our hypothesis on the mediation role of CC16 in this association, however our results encourage further exploration of this possibility in future studies. •Need of long-term studies on the effects of air pollution exposure on lung function throughout childhood•We aimed to identify CC16 as a biomarker mediating the association between air pollution and lung health•Increasing prenatal PM10 and PMcoarse are associated with lower childhood FVC and FEV1•Prenatal air pollution exposure impacts childhood lung function more than postnatal•Increasing CC16 levels at age 4 are related to increased childhood lung function growth